Sudachi peel extract powder including the polymethoxylated flavone sudachitin improves visceral fat content in individuals at risk for developing diabetes. Issue 8 (15th June 2021) - Shikishima, Yasuhiro; Tsutsumi, Rie; Kawakami, Ayuka; Miura, Hiroyuki; Nii, Yoshitaka; Sakaue, Hiroshi
Abstract: In vitro and animal studies have indicated that extracts from the peel of the Japanese Citrus sudachi, including sudachitin, ameliorate hyperlipidemia and reduce obesity. Sudachitin, a polymethoxylated flavone, has been reported as having favorable effects on lipid and glucose metabolism but results from clinical trials have been inconsistent. The aim of this study was to determine the effect of consuming capsules of sudachi peel extract powder on visceral fat in Japanese men and women in a randomized controlled trial. This was a 12‐week randomized, double‐blind, placebo‐controlled trial involving 41 participants aged 30–65 years with BMI 23–30 kg/m 2, randomly allocated to receive either sudachi peel extract powder (sudachitin 4.9 mg/day, n = 21) or placebo ( n = 20) of identical appearance. The primary outcome measure was visceral fat mass, assessed during intervention. Thirty‐eight of the 41 subjects completed the protocol. Compared with placebo, sudachi peel extract powder significantly reduced the ratio of visceral fat to subcutaneous fat, and moderately reduced waist circumference, a metabolic syndrome marker. Glycemic control and lipid profile were not changed significantly in these subjects. Consumption of capsules of sudachi peel extract powder favorably improves the ratio of visceral fat to subcutaneous fat in individuals at risk for developing diabetes, especially in individuals with large visceral fat area, while not adversely affecting glycemic control. Abstract : Extracts of Citrus sudachi (sudachi) peel, containing the polymethoxylated flavone sudachitin, have shown promise in vitro and in animal models. Compared with placebo, sudachi peel extract significantly reduced the ratio of visceral fat to subcutaneous fat (−0.0265%, p = .0485), and moderately reduced visceral fat and waist circumference.